Evaluative Study of Educational Administrative Facilities: Comparison Between Departments at Polytechnic XYZ - Fawwaz, Faisa; Sanjaya, Rio; Chaniago, Harmon (International Journal Administration, Business & Organization, 2025)
Administrative facilities and infrastructure play a vital role in supporting the smooth academic process in higher education institutions. This study aims to compare the completeness of administrative facilities and infrastructure between two departments within the same institution. A comparative method was used through direct observation of the physical conditions in both departments. The results show that Department A meets 93% of the facility indicators, while Department B meets 83%. Department A is equipped with tools such as a fax machine, microwave, and perforator, whereas Department B only has a coffee machine. In terms of infrastructure, Department A meets all indicators (100%), including restroom availability, while Department B meets 88% due to the absence of a restroom. The administrative room in Department A is more crowded and less organized because it manages seven study programs, unlike Department B, which manages only two and appears tidier. Both departments face issues with lighting and air circulation due to constantly closed windows, despite having air conditioning. This study recommends improving spatial management in Department A and adding restroom facilities in Department B. Enhancing natural lighting and ventilation is also advised to improve staff comfort and well-being. The findings highlight the existing gap in facilities between departments and serve as a valuable reference for management in planning equitable and efficient facility development in the future.